2014
DOI: 10.1080/19338244.2014.988673
|View full text |Cite
|
Sign up to set email alerts
|

Status and determinants of individual actions to reduce health impacts of air pollution in US adults

Abstract: Although regulation of emissions is the primary strategy to reduce air pollution-related morbidity, individual-level interventions are also helpful in mitigating health impacts. We used data from 2007-2008 National Health and Nutrition Examination Survey to study the prevalence of individual-level action among the US adult population if informed of air pollution, and to see if this differed by demographic and health factors. Only 13.5% (95% confidence interval [CI]: 11.6-15.4%) of participants aware of air qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
1
18
0
2
Order By: Relevance
“…In general, these results are consistent with previous studies recognising wearable devices as possible facilitators, and not necessarily drivers, of health behaviours [ 80 ], where engagement strategies [ 17 ] and message tailoring [ 78 , 79 ] may be the key to successful health messages, particularly when these messages address people’s beliefs about the health threat and the advice [ 81 ]. Finally, it is worth noting that whilst a growing body of research is showing that air quality warnings have the potential to reduce hospitalisation due to respiratory symptoms, as well as reduce to some extent outdoor physical activities during air alert days [ 7 , 53 , 82 93 ], we cannot be entirely sure that these observed behaviours are primarily driven by the warnings themselves rather than people’s own perception of bad air quality or perhaps a combination of the two. This is because these studies are mainly based on the assumption that everyone is exposed to air quality alerts when these are issued.…”
Section: Discussionmentioning
confidence: 98%
“…In general, these results are consistent with previous studies recognising wearable devices as possible facilitators, and not necessarily drivers, of health behaviours [ 80 ], where engagement strategies [ 17 ] and message tailoring [ 78 , 79 ] may be the key to successful health messages, particularly when these messages address people’s beliefs about the health threat and the advice [ 81 ]. Finally, it is worth noting that whilst a growing body of research is showing that air quality warnings have the potential to reduce hospitalisation due to respiratory symptoms, as well as reduce to some extent outdoor physical activities during air alert days [ 7 , 53 , 82 93 ], we cannot be entirely sure that these observed behaviours are primarily driven by the warnings themselves rather than people’s own perception of bad air quality or perhaps a combination of the two. This is because these studies are mainly based on the assumption that everyone is exposed to air quality alerts when these are issued.…”
Section: Discussionmentioning
confidence: 98%
“…Lissåker et al found that certain groups including the elderly and those with either respiratory or cardiovascular disease are more likely to change behaviors when they are aware of poor air quality [48]. This suggests that some of the most susceptible groups do, in fact, take measures to protect themselves against air pollution; unfortunately, the authors also noted that most people did not alter their behavior.…”
Section: Interventions To Reduce Air Pollution Exposures At a Personamentioning
confidence: 99%
“…For example, symptoms are higher among persons with low level of education and members of minority groups (Lissåker et al 2014; Orru et al 2015). This relationship has been explained by the capacity to cope with risks related to one’s physical or psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Aspects that may modify risk perception include social status and level of perceived control a person has over one’s wellbeing, and are thereby important predictors of health symptoms. For example, symptoms are higher among persons with low level of education and members of minority groups (Lissåker et al 2014 ; Orru et al 2015 ). This relationship has been explained by the capacity to cope with risks related to one’s physical or psychological well-being.…”
Section: Introductionmentioning
confidence: 99%